Re-visiting the NVQ debate: 'bad' qualifications, expansive learning environments and prospects for upskilling workers - Cox, A (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2007)
NVQs have endured nearly two decades of criticism on philosophic and practical grounds. This paper uses qualitative evidence to report the impact of this qualification for groups of lower grade staff working in the healthcare sector and finds beneficial effects on acquisition of knowledge and skills, personal attributes and pay and career progression. It analyses the reasons for the apparent success of the qualification and argues that this lies in specific features of the workplaces concerned which were partly fulfilling criteria for an 'expansive' orientation to workforce development. These included provision of multiple sources of organisational support for learner, careful design and quality monitoring of associated learning interventions and alignment of development for individual and organisational goals leading to opportunities for career progression. This consequently led to higher than usual exposure to learning interventions for NVQ participants and more reported 'learning' taking place. It concludes by considering the prospects for the NVQ, what we can learn from these settings about effecive skills development strategies and the prospects for replication of these outcomes in the wider economy.